2022
DOI: 10.4055/cios21250
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Thigh Pain Following Minimally Invasive Oblique Lateral Interbody Fusion: Multivariate Analysis from a Prospective Case Series

Abstract: Background Oblique lateral interbody fusion (OLIF) involves the antepsoas approach and psoas major muscle (PMM) retraction to insert the interbody cage orthogonally. Therefore, OLIF is often associated with postoperative anterior thigh pain (ATP) on the approach side. However, there is limited evidence on the nature and risk factors of ATP following OLIF. Methods Consecutive patients who planned to undergo minimally invasive OLIF and percutaneous pedicle screw instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
7
2
Order By: Relevance
“…However, our results indicate that hematoma in the psoas major muscle and cage malposition were associated with the development of thigh symptoms and muscle weakness, respectively. Although Chang et al 21 reported that cage subsidence was more frequent in patients with thigh pain (27.5% vs. 11.9%), no association with thigh symptoms was found in our investigation.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…However, our results indicate that hematoma in the psoas major muscle and cage malposition were associated with the development of thigh symptoms and muscle weakness, respectively. Although Chang et al 21 reported that cage subsidence was more frequent in patients with thigh pain (27.5% vs. 11.9%), no association with thigh symptoms was found in our investigation.…”
Section: Discussioncontrasting
confidence: 92%
“…Surgery at the L4/5 level 15–17 and surgical duration 18,19 were previously reported as factors associated with the development of thigh symptoms. Other reports indicate that the L2/3 level, thinning of the psoas major muscle, and retraction time on the psoas major muscle are the risk factors for thigh paresthesia, 20 thigh sensory change, 13 and severe thigh pain 21 . However, our results indicate that hematoma in the psoas major muscle and cage malposition were associated with the development of thigh symptoms and muscle weakness, respectively.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…26,27 The amount of psoas muscle retraction is also reported to be associated with the anterior thigh symptom in OLIF at the L4-5 level. 28 Aggressive and prolonged retraction may cause more severe postoperative anterior thigh symptoms. Care should be taken during the psoas muscle manipulation in order to expose the targeted intervertebral disc.…”
Section: Discussionmentioning
confidence: 99%
“…Other intraoperative complications, which occur in less than 1% of cases, include major vascular injury, vertebral body fracture, membrane laceration, and ureteral injury. The most common immediate postoperative complications are transient numbness or pain in the lower limbs, as well as temporary weakness and nerve deficits arising from sympathetic trunk injury [ 127 , 128 ]. However, a review demonstrated significant benefits via a modified OLIF procedure through the anteroinferior psoas approach that resulted in reduced psoas and neurovascular injury, as well as improved pain scores [ 129 ].…”
Section: The Oblique Lumbar Interbody Fusion (Olif)mentioning
confidence: 99%